Criopreservação de tecido testicular bovino adulto: da evidência científica a avaliação das técnicas de congelação e vitrificação - Joaquim, Gabriela da Silva Carvalho (2024)
The aim of this study was to establish an efficient method for cryopreserving bovine testicular fragments. To this end, 24 fragments of 1.0 cm3 obtained from five pairs of testicles were used and randomly assigned to different treatments: Fresh testicular tissue fragments or control (TTF), slow freezing 1 (CL1 - equilibrated at 4°C and -20°C for 2 hours), slow freezing 2 (CL2 - transferred directly to freezer at -80°C), vitrification 1 (Vit1 - ovariam tissue cryosystem - OTC), vitrification 2 (Vit2 - Solid Surface Vitrification SSV) and vitrification 3 (Vit3 - directly in cryotubes). After thawing or heating, the testicular fragments were fixed and processed for morphological and morphometric analysis (histology), collagen fibers (picrosirius), cell proliferation and DNA repair. The morphological results showed that the cryopreservation process caused greater damage (p<0.001) in all treatments (CL1, CL2, Vit1, Vit2 and Vit3) compared to TTF. When the treatments were compared to each other, Vit3 caused significantly greater damage compared to all the other treatments (CL1 p<0.001; CL2 p=0.006; Vit1 p=0.010; Vit2 p=0.008). As for tubular diameter, CL2 (p=0.003), Vit1 (p<0.001), Vit2 (p=0.012) and Vit3 (p<0.001) were smaller compared to TTF. The percentage of cells immunolabeled for PCNA was significantly lower in CL1 (p< .001) compared to CL2 (p< .001), Vit1 (p< .001) and Vit2 (p< .014). In addition, Vit2 and Vit1 showed a significant reduction compared to CL1 (p=0.003) and CL2 (p< .001) and Vit1 (p< .004), respectively. The percentage of type III collagen fibers was significantly lower in Vit3 when compared to TTF (p=0.005), CL1 (p<.001), CL2 (p< .001), Vit1 (p=0.001) and Vit2 (p=0.003). With this, we conclude that vitrification proved to be equally effective to the slow freezing protocols already established in the literature for the cryopreservation of adult bovine testicular tissue. The OTC device and the SSV technique were the most efficient for storing this type of tissue.